Effects of Female Hormone Use and Birth Control Contraceptives on Depression (P11-017-19) - Wingeier, Madeleine (Curr Dev Nutr, 2019)
OBJECTIVES: Research has shown that fluctuation of estrogen and other hormones in the body can enhance the body's response to stress, which in turn, can lead to both depression and anxiety. The main objectives of this study were to explain the association of the use of female hormones with the likelihood of getting depression and to describe the association of the use of birth control contraceptives with the likelihood of getting depression. The study hypothesized that the uses of female hormones and contraceptive birth control were likely to increase the risk of developing depression or depressive symptoms. The study also looked at how special dietary status was likely to affect the use of either female hormones or contraceptive birth control. METHODS: Data came from the National Health and Nutrition Examination Survey (NHANES) between 2009 and 2016, and the study included female participants aged 18 years and older who were pregnant or had ever been pregnant. Multivariate regression analyses were used to investigate the effect of the use of female hormones or contraceptive birth control on depression. RESULTS: Results showed that the use of female hormones was associated with higher risk of depression, so women who used female hormones seem to have increased risk of developing depression. The use of birth control with higher amounts of estrogen were likely to increase the risk of developing depression in women who have ever been pregnant, and those who had longer duration of the use of birth control were also at higher risk of depression. In addition, women with low-fat diet were at higher chance of using either female hormones or contraceptive birth control. CONCLUSIONS: Women are at greater risk for depression than men, and reproductive events such as postpartum and menopausal transition also likely cause the risk of depression. Therefore, women should have better understanding about different forms of birth control and female hormones and about long-term health complications such as increased risk of breast and cervical cancer. FUNDING SOURCES: None.